2011
DOI: 10.3357/asem.3034.2011
|View full text |Cite
|
Sign up to set email alerts
|

Civilian Pilot Exposure to Ultraviolet and Blue Light and Pilot Use of Sunglasses

Abstract: Population and animal studies indicate that long-term exposure to short-wavelength visible light and ultraviolet (UV) radiation causes increased risk of certain ocular pathologies such as cataracts and maculopathy. The potential risk to flight crew is unknown. The UK Civil Aviation Authority (CAA) has issued guidance to pilots regarding sunglass selection; however, it is not known if this guidance is appropriate given pilots' unique occupational environment. A search and appraisal of the relevant literature wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Regarding physical loads, the prolonged and cumulative UV exposure is knowingly harmful to the eyes (26) and skin. While developing their work, the CHAs most frequently expose their faces, necks, arms, legs, hands and eyes to solar radiation, which are regions more prone to skin changes.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding physical loads, the prolonged and cumulative UV exposure is knowingly harmful to the eyes (26) and skin. While developing their work, the CHAs most frequently expose their faces, necks, arms, legs, hands and eyes to solar radiation, which are regions more prone to skin changes.…”
Section: Discussionmentioning
confidence: 99%
“…noted some evidence of increased melanoma occurrence in professional pilots. Chorley et al [196] . concluded that pilots flying in daylight hours are exposed to solar radiation that is 2 or 3 times greater at cruising altitudes compared to exposures at sea level.…”
Section: Occupational Health Hazards and Effects Related To Climate Cmentioning
confidence: 99%
“…UVR exposure is associated with cataract formation (12,16,30); however, evidence of increased prevalence of cataracts in pilots is limited (6). There is some evidence (21,37) of a relationship between UV-A exposure and melanocytic skin cancers which, if present on the eyelids, can have significant effect to comfort or vision.…”
Section: Introductionmentioning
confidence: 99%
“…This translates to a two to three times increase in UVR between sea level and an airline cruise altitude of 35,000 ft (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation